2021
DOI: 10.18488/journal.23.2021.102.94.104
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Module as a Strategic Solution to Enhance Creativity in the Teaching of Writing

Abstract: The 4 th Industrial Revolution (4IR) focuses on human capital growth in educational settings. This leads to the demand for educators who can bring creative temperaments to English Language teaching as mentioned in the National Education Blueprint (NEP) and Integrated Curriculum for Secondary School (KSSM) in line with the 21 st Century Teaching and Learning philosophy. Despite a pool of pedagogical tools and ideas available to teach writing creatively, some teachers still lack creativity skills and knowledge t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…According to Arnon and Reichel (2007), the two main elements of ideal teachers are personal qualities and subject knowledge. In the study in which educational philosophers revealed various images of ideal teachers, supporting the cognitive development of students was identified as the main task of an ideal teacher (Gopal & Singh, 2020;Yunus et al, 2021). Ko and Sammons (2013) state that other important aspects include the current social, behavioral, and emotional goals and objectives of education.…”
Section: The Ideal Teacher and The Ideal Pre-service Mother Tongue Te...mentioning
confidence: 99%
“…According to Arnon and Reichel (2007), the two main elements of ideal teachers are personal qualities and subject knowledge. In the study in which educational philosophers revealed various images of ideal teachers, supporting the cognitive development of students was identified as the main task of an ideal teacher (Gopal & Singh, 2020;Yunus et al, 2021). Ko and Sammons (2013) state that other important aspects include the current social, behavioral, and emotional goals and objectives of education.…”
Section: The Ideal Teacher and The Ideal Pre-service Mother Tongue Te...mentioning
confidence: 99%
“…Those images usually revolved around the basic qualities and values. It is the teacher's role to promote student cognitive development (Gopal & Singh, 2020;Yunus et al, 2021). This is also viewed as one of the prime purposes of education and teaching.…”
Section: Qualities Of An Ideal Teachermentioning
confidence: 99%
“…The need to plan for an integrated approach to the teaching and learning of the writing skills was felt to assist the weak learners and the teacher concerned (Palpanadan, Abdul Rahim Salam & Fauziah Ismail, 2014;Yunus et al, 2021). It was decided that a set of modules for the teaching and learning of writing would satisfy the need.…”
Section: Background To the Problemmentioning
confidence: 99%